GrADE: Grade and Assessment Dashboard for Educators/ Azmi Salim ... [et al.] - Salim, Azmi; Solat, Naliza; Abdullah @ Baharum, Mohd Amli; Saad, Zuria Akmal; Mohd Mokhtar, Noorsuraya; Abdullah, Mohd Zulkifli (2023)
A standardized platform for recording student’s assessment marks is paramount in today’s education. Not only does it assure consistency, which reduces grading biases, but it also guarantees fairness in the evaluation process. The project aims to develop a standardized platform that streamlines the dissemination of assessment marks, which can support educators and the student’s academic journey. By uploading and updating assessment scores promptly on the platform, the lecturers can identify areas for improvement, and the students are able to engage throughout the semester, thus fostering academic excellence fully. This project aims to give students early access to performance evaluations. The integration of technology being used in developing this platform enables real-time accessibility of assessment marks. This allows the students to view their marks directly, moving away from traditional paper-based mark distribution and enabling them to receive immediate and accurate feedback. This platform also focuses on encouraging educators to embrace technology and online platforms in displaying assessment marks, thus motivating the lecturers to adopt digital solutions for assessment management and promoting efficiency in the educational process. The proposed standardized platform can revolutionize the assessment process, benefiting both students and educators by fostering a dynamic and transparent learning environment. Through integrating technology and a commitment to transparency, this platform also seeks to empower learners, enable them to reach their full academic potential, and elevate the overall learning experience.